Love me, love me not. Vol. 2 - Sakisaka, Io; Thistlethwaite, Nancy (Shojo beat manga., 2020)
"Fast friends Yuna and Akari are complete opposites--Yuna is an idealist, while Akari is a realist. When lady-killer Rio and the oblivious Kazuomi join their ranks, love and friendship become quite complicated!... Love and friendship have become quite complicated for these four friends. Yuna has fallen in love with Rio, but he has feelings for Akari that he's never been able to express. While Yuna keeps his secret, Akari makes a move on the person she's interested in."--Provided by publisher.